Successful pandemic management through computer science: a case study of a financial corporation with workers on premises - Partida-Hanon, Angélica; Díaz-Garrido, Ramón; Mendiguren-Santiago, José María; Gómez-Paredes, Laura; Muñoz-Gutiérrrez, Juan; Miguel-Rodríguez, María Antonia; Reinoso-Barbero, Luis (Frontiers in Public Health, 2023)
Background: In November 2019, an infectious agent that caused a severe acute respiratory illness was first detected in China. Its rapid spread resulted in a global lockdown with negative economic impacts.In this regard we expose the solutions proposed by a multinational financial institution that maintained their workers on premises, so this methodology can be applied to possible future health crisis.Objectives: To ensure a secure workplace for the personnel on premises employing biomedical prevention measures and computational tools.Methods: Professionals were subjected to recurrent COVID-19 diagnostic tests during the pandemic.The sanitary team implemented an individual following to all personnel and introduced the information in databases. The data collected was used for clustering algorithms, decision trees and networking diagrams to predict outbreaks in the workplace. Individualized control panels assisted the decisionmaking process to increase, maintain or relax restrictive measures.Results: 55789 diagnostic tests were performed. A positive correlation was observed between the cumulative incidence reported by Madrid's Ministry of Health and the headcount. No correlation was observed for occupational infections, representing 1.9% of the total positives. An overall 1.7% of the cases continued testing positive for COVID-19 after 14 days of quarantine.Based combined approach of medical and computational science tools, we propose a management model that can be extended to other industries that can be applied to possible future health crises. This work shows that this model resulted in a safe workplace with a low probability of infection among workers during the pandemic.